IPTEK BAGI MASYARAKAT (IbM) PENYULUHAN TENTANG PEMBERIAN MAKANAN TAMBAHAN (PMT) PADA BALITA DI WILAYAH KERJA PUSKESMAS MULTIWAHANA PALEMBANG TAHUN 2016 - Pastuty, Rosyati; Sumastri, Heni (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2020)
Malnutrition is a major problem in the world that does not only occur in developing countries but also in developed countries (Freeman L). More than 3.5 million mothers and children under five every year are caused by malnutrition, and millions more experience permanent physical and mental disabilities as a result of lack of food intake in early life (Lancet, 2011). Based on the 2013 Riskesdas data, the prevalence of undernutrition was 12.1% in 2013. In the province of South Sumatra in 2013 the prevalence of undernutrition in children under five was 12.1% (Ministry of Health, 2014). In children under five with malnutrition, efforts need to be made so that they do not become malnourished and even increase their nutritional status. The effort that needs to be done is by providing additional food (PMT) for recovery (Kemenkes RI, 2011). PMT Recovery is intended as an addition, not as a substitute for the main daily meal. The PMT is based on local food ingredients with regional specialties adapted to local conditions (Directorate General of Nutrition and Maternal and Child Health, Ministry of Health, RI, 2012). This community service aims to improve the nutritional status of toddlers in the work area of ​​the Multiwahana Palembang Health Center by conducting counseling and distributing leaflets/posters about the Provision of Supplementary Foods (PMT) to toddlers to mothers who have babies and toddlers in the work area of ​​the Palembang Multiwahana Health Center. During the outreach activities, the community was very enthusiastic about listening and asking questions about good eating for infants and toddlers. This community service is expected to increase the knowledge and skills of the community in improving the nutritional status of toddlers by providing additional food according to the age of infants and toddlers.